Russo-Georgian War (2008): the field technological innovation - Caixeta Arraes, Virgílio (2020)
This article deals with the war between Russia and Georgia in 2008 referring to the confrontation in South Ossetia and Abkhazia, russophiles and secessionists territories. The conflict would be another traditional episode in the international system, but the use of cybernetics in large scale by the Russians gave it singularity. Thus, this war was an example of the damage caused to Georgia as a victim of cybernetics as military weapon.